Examining the impact of inter-provincial migration on environmental health in China. (17th February 2021) - Yang, Yu-Ou; Hou, Juan-Juan; Chen, Xin-Yu; Yu, Shi-Wei; Zhang, Jiu-Tian; Liu, Lan-Cui
Abstract: China has a large volume of inter-provincial migrants, accounting for more than 11% of the total population. The economic benefits of inter-provincial migration have been well studied, whereas the health impacts related to environmental factors are generally ignored. In this study, the exposure-response function was used to estimate the health effects and the corresponding economic value was calculated by the adjusted-human-capital and cost-of-illness methods. Considering a scenario without personal protection, inter-provincial migration resulted in a reduction of 6114 premature deaths, 233.4 thousand hospitalization cases, and 1.5 million asthma attacks due to the PM2.5 population-weighted exposure decreasing by 3.94 μ g m −3 in 2015. The avoided economic value of these health benefits was 0.02% of the national GDP in 2015. However, two-fifths of inter-provincial migrants whose destinations are areas with heavier pollution suffered greater health losses at the regional level. Additionally, personal protection does not significantly reduce the health loss. Thus, national pollution control measures are required to curb air pollution.